Adherence to Medical Nutrition Therapy: From Barriers to Bridgers - Sanjay Kalra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Type 2 diabetes is a major clinical and public healthdisorder worldwide.1 While multiple drugs are nowavailable for its treatment, no management strategy can besuccessful without nutritional and dietary intervention. Thenature of lifestyle-related interventions including diet, issuch that they intrude into one’s preferred way of life. Suchtherapies, therefore, are associated with lower adherenceand persistence.2 In medicine, we are trained to take a history and evaluatepossible causes of a condition before planning ourtreatment. Similarly, in diabetes care, we must find thecausative and contributory factors that influence aparticular lifestyle choice. This step is essential to build asustainable and sufficient diabetes care ecosystem. Continued...